I'll show them who's boss : series 2 - BBC Worldwide (North Sydney: BBC Worldwide, 2023)
I'll Show Them Who's Boss - Series 2 tells you how to turn a business around - ruthlessly. Gerry Robinson is a straight talking businessman with a hard-nosed reputation that always precedes him.